2020
DOI: 10.1242/dev.185595
|View full text |Cite
|
Sign up to set email alerts
|

Single cell sequencing of radial glia progeny reveals the diversity of newborn neurons in the adult zebrafish brain

Abstract: Zebrafish display widespread and pronounced adult neurogenesis, which is fundamental for their regeneration capability after central nervous system injury. However, the cellular identity and the biological properties of adult newborn neurons are elusive for most brain areas. Here, we have used short-term lineage tracing of radial glia progeny to prospectively isolate newborn neurons from the her4.1 + radial glia lineage in the homeostatic adult forebrain. Transcriptome analysis of radial glia, newborn neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 87 publications
10
92
0
Order By: Relevance
“…The proliferative response of the injured zebrafish telencephalon is driven by the RGCs and reaches a peak at the lesioned site around 3 dpl ( Marz et al, 2011 ; Kizil et al, 2012c ). At this stage, we observed that some quiescent RGC genes such as fabp7a , mt-atp8 , hipk1a , s100b , and mgll were upregulated in both hemispheres, while ptn , luzp2 , psap , hepacama , and anxa11b were only upregulated in the lesioned side ( Kaslin et al, 2017 ; Lange et al, 2020 ). On the other hand, proliferating RGC genes including tmsb4x , hmgb2a , hmga1a , rps23 , and ran were exclusively upregulated in the lesioned half, whereas the general proliferation marker ccnd1 was upregulated in both halves ( Lange et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The proliferative response of the injured zebrafish telencephalon is driven by the RGCs and reaches a peak at the lesioned site around 3 dpl ( Marz et al, 2011 ; Kizil et al, 2012c ). At this stage, we observed that some quiescent RGC genes such as fabp7a , mt-atp8 , hipk1a , s100b , and mgll were upregulated in both hemispheres, while ptn , luzp2 , psap , hepacama , and anxa11b were only upregulated in the lesioned side ( Kaslin et al, 2017 ; Lange et al, 2020 ). On the other hand, proliferating RGC genes including tmsb4x , hmgb2a , hmga1a , rps23 , and ran were exclusively upregulated in the lesioned half, whereas the general proliferation marker ccnd1 was upregulated in both halves ( Lange et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…At this stage, we observed that some quiescent RGC genes such as fabp7a , mt-atp8 , hipk1a , s100b , and mgll were upregulated in both hemispheres, while ptn , luzp2 , psap , hepacama , and anxa11b were only upregulated in the lesioned side ( Kaslin et al, 2017 ; Lange et al, 2020 ). On the other hand, proliferating RGC genes including tmsb4x , hmgb2a , hmga1a , rps23 , and ran were exclusively upregulated in the lesioned half, whereas the general proliferation marker ccnd1 was upregulated in both halves ( Lange et al, 2020 ). Besides, we found that many cell cycle-associated genes such as pcna , mki67 , rpl35 , mdka , ccna2 , and cdk1 were upregulated predominantly in the lesioned hemisphere ( Sobecki et al, 2017 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However so far only low numbers of stem cells were captured in scRNAseq experiments conducted on the hippocampus, which prevents proper analysis of their intrinsic heterogeneity. Two reports were recently published in zebrafish, based on NSCs isolated from her4.1-driven transgenes (Cosacak et al, 2019;Lange et al, 2020). However these studies only captured small numbers of NSCs (609 and 76, respectively).…”
Section: Nsc Quiescence Is a Heterogeneous Statementioning
confidence: 99%
“…These observations suggest that oligodendrocytes are produced within the parenchyma from OPCs. A recent publication based on scRNAseq argues that her4.1-positive NSCs express olig2 at very low level, suggesting nascent NSC progeny differentiating toward OPCs (Lange et al, 2020). Likewise, pseudo-lineages inferred from scRNAseq in the mouse SEZ reveal a molecular connection between NSCs and oligodendrocytes (Mizrak et al, 2019).…”
Section: Nsc Potency: Do Nsc Fates Differ Between Zebrafish and Mouse?mentioning
confidence: 99%